Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1155/2017/4247853
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Human Respiratory Viruses and Lack of MERS-Coronavirus in Patients with Acute Upper Respiratory Tract Infections in Southwestern Province of Saudi Arabia

Abstract: We undertook enhanced surveillance of those presenting with respiratory symptoms at five healthcare centers by testing all symptomatic outpatients between November 2013 and January 2014 (winter time). Nasal swabs were collected from 182 patients and screened for MERS-CoV as well as other respiratory viruses using RT-PCR and multiplex microarray. A total of 75 (41.2%) of these patients had positive viral infection. MERS-CoV was not detected in any of the samples. Human rhinovirus (hRV) was the most detected pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The findings are also consistent with other studies among travelers and pilgrims where influenza far exceeded MERS [36][37][38][39][40]. Similarly, in a small study in Saudi Arabia, influenza viruses were detected in 16% of 182 patients [29]. Similarly, among a small study of 52 suspected MERS cases in the United States of America, Influenza was the most commonly (35%) identified respiratory agent [41] and another study found influenza A and B in 11% of 296 investigated patients [26].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings are also consistent with other studies among travelers and pilgrims where influenza far exceeded MERS [36][37][38][39][40]. Similarly, in a small study in Saudi Arabia, influenza viruses were detected in 16% of 182 patients [29]. Similarly, among a small study of 52 suspected MERS cases in the United States of America, Influenza was the most commonly (35%) identified respiratory agent [41] and another study found influenza A and B in 11% of 296 investigated patients [26].…”
Section: Discussionsupporting
confidence: 88%
“…In the South Korea outbreak, 184 (1%) had MERS among 16,752 suspected cases [28]. In a small study from Saudi Arabia, MERS-CoV was not detected in 182 cases tested November 2013 and January 2014 (winter time) [29]. Thus, the overall positivity of MERS-CoV among a large cohort remains low.…”
Section: Discussionmentioning
confidence: 99%
“…Remaining NP samples were used for complementary DNA (cDNA) synthesis and microarray testing as described previously . Nucleic acid was extracted from all samples and used to synthesize cDNA using SuperScript III First‐Strand Synthesis SuperMix Kit (Life Technologies, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Nucleic acid was extracted from all samples and used to synthesize cDNA using SuperScript III First‐Strand Synthesis SuperMix Kit (Life Technologies, Carlsbad, CA). All samples were then tested for hCoVs (HKU1, OC43, NL63, and 229E), influenza viruses (flu A, flu B, and flu A/H1N1), hRV (A and B), human parainfluenza viruses (hPIV) (1, 2, 3, and 4), human metapneumovirus (hMPV) (A and B), enterovirus (EV) (A, B, C, and D), human adenoviruses (hAdv) (A, B, C, and E), and human respiratory syncytial virus (hRSV) (A and B) using Infiniti RVP Plus Assay on Infiniti Plus Analyzer (AutoGenomics Inc., Carlsbad, CA) according to manufacturer's instructions and as previously described . Samples were considered positive when the ratio between the virus and background signals was above the calculated threshold.…”
Section: Methodsmentioning
confidence: 99%
“…To date, six human coronaviruses have been discovered, i.e., the human coronaviruses OC43 and 229E, NL63 and HKU1, and the SARS and MERS coronaviruses. Except for the latter two, all human coronaviruses have been noted to occur worldwide and are mostly associated with a seasonality that follows the typical flu-like symptom season [23][24][25][26][27][28][29][30][31]. As the nomenclature of coronaviruses is far from being logical, these viruses are described in the next section in more detail according to their systematic order.…”
Section: Epidemiologymentioning
confidence: 99%